2020
DOI: 10.3390/brainsci10030154
|View full text |Cite
|
Sign up to set email alerts
|

Depression Treatment Status of Economically Disadvantaged African American Older Adults

Abstract: Background: It is known that depression remains largely untreated in underserved communities. Hence, it is desirable to gain more knowledge on the prevalence and correlates of untreated depression among African-American (AA) older adults in economically disadvantaged areas. This knowledge may have the public health benefit of improving detection of AA older adults with depression who are at high risk of not receiving treatment, thereby reducing this health disparity. Objective: To study health and social corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…All participants had at least one chronic medical condition and were aged sixty-five or older. For more information on the methodology of this study, please see our previous publications [ 21 , 22 , 23 , 24 , 25 ]. The sample size included 724 individuals (116 Latinx and 608 Black).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants had at least one chronic medical condition and were aged sixty-five or older. For more information on the methodology of this study, please see our previous publications [ 21 , 22 , 23 , 24 , 25 ]. The sample size included 724 individuals (116 Latinx and 608 Black).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic medical conditions (CMCs) included: (1) stomach or intestinal problems; (2) asthma or bronchitis; (3) arthritis; (4) hypertension/high blood pressure; (5) heart diseases; (6) diabetes; (7) chronic back pain; (8) cancer; (9) endocrine conditions and thyroid problems; (10) stroke; and (11) migraine/headache. The number of CMCs was measured by asking whether participants have been diagnosed with the conditions listed above [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…For more information on methodology of this study, please see our previous publications. [19][20][21][22][23] The sample size was 734 individuals (118 Latino and 616 African American).…”
Section: Participants and Samplingmentioning
confidence: 99%
“…The number of CMCs was measured by asking whether participants have been diagnosed with the conditions listed above. [19][20][21][22][23] Outcome SRH was measured using conventional single-item measure. Poor SRH was coded as 1, and fair, good, very good, and excellent health was coded as 0.…”
Section: Independent Variablementioning
confidence: 99%
“…1 As an increasing number of Americans are diagnosed with depression annually, 2 there is a growing number of studies documenting a substantial number of patients that are unable to receive treatment. 3,4 Researchers have documented how depression may affect various aspects of patients' lives, such as lower employment rates, job productivity, and disrupted family function. [5][6][7] Unfortunately, prior research has shown that low-income populations observe challenges in receiving access to mental health care.…”
Section: Introductionmentioning
confidence: 99%